Analisa Pengaruh Jenis Bahan Bakar Terhadap Efisiensi Boiler Type Chain Grate Stoker - Firmansyah, Muhammad Aditya Fitra; Effendi, Mohammad (LPPM Universitas Madako Tolitoli, 2025)
Boilers are essential components in industry, functioning to generate steam for production processes, and their efficiency greatly affects both energy effectiveness and operational costs. One of the main factors influencing efficiency is the type of fuel used. This study aims to analyze the effect of fuel variations on the efficiency of a Chain Grate Stoker boiler in a textile industry located in Pandaan, Pasuruan Regency. The research employed a quantitative approach by testing five types of fuel, namely coal, wood pellets, candlenut shells, palm shells, and a coal–wood pellet mixture (80:20). Data were collected through direct measurement of boiler operational variables, including steam pressure, furnace temperature, feedwater temperature, and steam flow rate. Boiler efficiency was calculated using the heat balance method by comparing the fuel input energy with the output energy in the form of steam. The results show that wood pellets produced the highest efficiency at 57% with an average furnace temperature of 415 °C, although requiring higher fuel consumption (1,800 kg/h). Candlenut shells yielded the lowest efficiency at 39% due to their high moisture content. Pure coal demonstrated moderate efficiency of 46% but produced a large amount of ash residue. Meanwhile, the coal–wood pellet mixture provided the best balance, achieving 51% efficiency with lower fuel consumption (1,300 kg/h) and moderate ash residue. This study confirms that fuel type has a significant impact on boiler efficiency and operational sustainability. The coal–wood pellet co-firing strategy is recommended as a more economical and environmentally friendly alternative compared to single-fuel utilization